2022
DOI: 10.33545/27074447.2022.v4.i2a.50
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder in relation to associated factors of children in salah-addin province: Iraq

Abstract: Background: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by deficits in social communication and the presence of restricted interests and repetitive behaviors. Rising prevalence of autism spectrum disorders (ASD) in the last decades has led research to focus on the diagnosis and identification of factors associated with ASD. This paper sought for possible factors that put children at risk for ASD. In this study, we investigated the association between ASD and child factors in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…The study was aimed to investigate various social and environmental factors related to autism. It suggested that autism is a male predominance disorder with a male-tofemale ratio of 2.6:1, this is in consistence with a study done in Salah-addin / Iraq, where 81% of the autistic sample were male [9] . The same was reported by Ratto AB et al, who declared that there is really a higher frequency of ASD among males, with a ratio about 3:1, This figure had attributed to the familial patterns and genetic links that made it "protective" in girls.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The study was aimed to investigate various social and environmental factors related to autism. It suggested that autism is a male predominance disorder with a male-tofemale ratio of 2.6:1, this is in consistence with a study done in Salah-addin / Iraq, where 81% of the autistic sample were male [9] . The same was reported by Ratto AB et al, who declared that there is really a higher frequency of ASD among males, with a ratio about 3:1, This figure had attributed to the familial patterns and genetic links that made it "protective" in girls.…”
Section: Discussionsupporting
confidence: 75%
“…Family history of autism or other mental health disorders, appeared in this study, to be significantly associated with autism risk p= 0.0001 & p= 0.006 respectively. The same was observed in salah-addin province/Iraq in 2022 [9] . This might explain the genetic responsibility for autism, as declared in South Carolina Project for autism, where anomalies of chromosome 15 have arisen [14] .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation